2013
DOI: 10.4149/bll_2013_083
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokine levels of colon cancer patients before and after treatment

Abstract: Aims and background:In the present study, we investigated the associations between pre-and posttreatment levels of adiponectin, ghrelin, resistin, visfatin and leptin levels in malign and benign groups Methods and study design: 20 malign colon carcinoma groups and 20 benign groups were included in this study. Serum levels of leptin, adiponectin, resistin, ghrelin, and visfatin were measured by Elisa kits (Milipore Corporation, Billerica, MA, USA). Results: In the malign group, serum ghrelin (71.90±23.7) levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…However, the correlation between circulating Nampt level and clinical stage in colorectal cancer remains controversial. The serum Nampt level in the malign group (colon carcinoma) was not significantly different from that in the benign group 31 . Another recent study showed that there were no significant correlations between circulating Nampt level and the TNM staging for CRC, although patients with CRC had significantly higher level of serum Nampt than the control group both before and after adjustment for covariates (e.g.…”
Section: Discussionmentioning
confidence: 67%
“…However, the correlation between circulating Nampt level and clinical stage in colorectal cancer remains controversial. The serum Nampt level in the malign group (colon carcinoma) was not significantly different from that in the benign group 31 . Another recent study showed that there were no significant correlations between circulating Nampt level and the TNM staging for CRC, although patients with CRC had significantly higher level of serum Nampt than the control group both before and after adjustment for covariates (e.g.…”
Section: Discussionmentioning
confidence: 67%
“…Among the 11 studies, one was case-cohort study conducted in USA [31], while the other 10 studies were of case-control design conducted either in Asia [18, 21, 23, 25, 26, 28] or in Europe [24, 27, 29, 32]. Ten of the studies were matched for age and/or gender [18, 21, 23, 24, 2629, 31, 32] and 6 of them were adjusted for BMI additionally [21, 23, 24, 26, 27, 31].…”
Section: Resultsmentioning
confidence: 99%
“…Insulin, insulin-like growth factor-1 (IGF1), leptin, adiponectin, steroid hormones, and cytokines are some host factors associated with obesity that not only influences the initiation and progression of breast cancer, but also affects its response to therapies [114]. Reports reveal decreased adiponectin in breast and endometrial cancer and vice versa in non-small cell lung cancer, pancreatic, liver, prostate, gastric, renal cell carcinoma, and colon cancer [115,116,117,118]. Wei et al [119] performed a meta-analysis of 107 studies in a random effect model to analyze the levels of circulating adiponectin in cancer patients versus controls.…”
Section: Obesity Adiponectin and Cancer: Interplay Of Bigwigsmentioning
confidence: 99%